The Transmembrane Domain C of AMPA Receptors is Critically Involved in Receptor Function and Modulation - Terhag, Jan; Gottschling, Kevin; Hollmann, Michael (Frontiers in Molecular Neuroscience, 2010)
Ionotropic glutamate receptors are major players in synaptic transmission and are critically involved in many cognitive events. Although receptors of different subfamilies serve different functions, they all show a conserved domain topology. For most of these domains, structure-function relationships have been established and are well understood. However, up to date the role of the transmembrane domain C in receptor function has been investigated only poorly. We have constructed a series of receptor chimeras and point mutants designed to shed light on the structural and/or functional importance of this domain. We here present evidence that the role of transmembrane domain C exceeds that of a mere scaffolding domain and that several amino acid residues located within the domain are crucial for receptor gating. and desensitization. Furthermore, our data suggest that the domain may be involved in receptor interaction with transmembrane AMPA receptor regulatory proteins.